AESTHETIC VALUES OF SPORTS HIJABS DESIGNS BETWEEN MALAYSIAN AND INTERNATIONAL SPORTSWEAR BRAND - Husna Saaidin; Hisyam Zakaria; Suriati Saidan; Wan Nadhra Ixora, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Sportswear market, normally by slinky legging, crop tops and close-fitting apparel. (Viktoria Hermann, 2022). Recently, the value of sports hijabs in global modest fashion has been growing over the past few year about $368 billion (Hafsa Lodi, 2020). Traditional hijabs vary from basic scarves to intricate multi-layered pieces, offering a fluid silhoutte that covers the head and neck entirely. However, during various athletic activities, these garments can easily slip off or get caught, possing both a modesty concern and a safety risk for the user. In contrast, sports hijabs maintain the same level of coverage but have a snugger and more secure fit. (Palmer G.D., 2023). Objective of this research is to idenfity the aesthetic value design, features and function of each sports hijab designs in the market. The researcher conducted observations and analyses on two (2) distinct local brand who are focusing in sports hijabs. This paper aims to determine the visual aethetic design of sports hijabs by evaluating and comparing between international and local sportswear brand in various aspects including details, features and materials.